Miras hukukunda muvazaalı işlemler ve tabi olduğu hükümler - Denizhan, Sıddıka İncedal (My University, 2019)
Türk Hukukunda önemli bir yeri olan Muvazaa kavramı; iki tarafın gerçek iradesi ile dışa yönelik beyanları arasında ortaya çıkan uygunsuzluk hali olarak tanımlanabilir. Muris Muvazaası ise murisin mirascılarını miras hakkından mahrum bırakmak gayesiyle yaptığı işlemlerdir. Bu işlemler genellikle, murisin mirasçılarından mal kaçırmak amacıyla yaptığı; gerçekte bağış olan sözleşmeyi, tapuda resmi memur önünde satım olarak gösterdiği sözleşmelerdir. Muris sağlığında, mirasçılarının miras haklarını engellemek amacıyla, bağışlama ve satış sözleşmelerine başvurduğu gibi buna benzer başka işlemler (sözleşmeler) de yapabilmektedir. Mirasçıların murisin sağlığında yaptığı hukuki işlemlerde muvazaa bulunduğunu ileri sürmeleri dava yoluyla olacaktır. Miras bırakanın muvazaalı hukuki işlemi kesin hükümsüz olduğu için mirasçılar tarafından muvazaa iddiası herhangi bir zamanaşımı süresine tabi olmaksızın, her zaman ileri sürülebilecektir.Çalışmamızda yukarıda özet olarak ele aldığımız konular doktrin ve Yargıtay kararları açısından ayrıntılı olarak işlenecektir.

The concept of Fraudulent Transaction which has an important place in Turkish Law; It can be defined as the state of non-conformity between the real will of the two parties and their external statements. Fraudulent Transaction of the Heritage Leap is the process of depriving the inheritors of the inheritance of the legacy. These transactions are usually made by the heirs of the heir of the inheritance for the purpose of smuggling goods; in fact, the contract, which is a donation, the bidding on the deed in front of the official contracts.While the inheritor is alive, he/ she can also make other similar transactions (contracts) as he/ she has applied for forgiveness and sale contracts in order to prevent the inheritance rights of his/ her heirs.The prosecution's claim that the legacy of the inheritor of the legal proceedings during his/ her life is fraudulent transaction will be through the case. The fraudulent transaction of the inheritor is strictly void, so the claim of fraudulent act by the heirs can always be asserted without any limitation period.In our study, the topics discussed above will be elaborated in terms of doctrine and Supreme Court decisions.
Keywords: Civil law; Confidential Operation; Fraudulent Transaction; Gizli İşlem; Görünürdeki İşlem; Hidden Payer; Hukuk; Law; Medeni hukuk; Muvazaa; Registration; Saklı Paylı Mirasçı; Tescil; Visible Transaction